Hubungan antara pendidikan dengan persepsi wisatawan pantai nirwana Kelurahan Sulaa Kecamatan Betoambari Kota Baubau - Anggriyani, Wa Ode; Sadarun, Baru; Mansyur, Akhmad (Jurnal Sosial Ekonomi Perikanan, 2022)
This study aims to determine the relationship between education and touris tperceptions. The location forthe researchis Nirwana Beach, Sulaa Village, Betoambari District, Baubau City in September-October2020. The method used is accidental sampling and scoring. Data were collected using questionnaires,observation, and documentation. The data analysis used is descriptive and correlation coefficientanalysis. As a result, it was found that the perception of tourists on Nirwana Beach wasrated in a fairlygood category and the relationship between education and tourist perceptionson Nirwana Beach was0.941, indicating a very strong relationship because the value is closeto one.